Lavallé, Bernard (ed.). Máscaras, tretas y rodeos del discurso colonial en los Andes. Lima: IFEA-Instituto Riva-Agüero, 2005, 246 pp. - Rohner Stornaiuolo, Stephanie Danielle (2008)
Esta reseña no presenta resumen.